Improved Accessibility of Healthcare Facility Services by Vulnerable Populations - Mabalay, Adrian; De Guzman, Maricel V. (Journal of Regional and City Planning, 2024)
This study determined the capacity of healthcare facilities in the Philippines to provide accessible health services to vulnerable groups during the COVID-19 pandemic. The research addressed the urgent need to support vulnerable populations facing higher health risks and barriers in accessing healthcare services. Using a cross-sectional, descriptive quantitative research design and the Healthcare Facility Capacity Self-Assessment on the Accessibility of Services for Vulnerable Populations survey, the researchers collected data from 154 participating healthcare facilities in the Philippines. The most important finding revealed significant gaps in the healthcare facilities’ capacity to serve vulnerable groups, particularly in physical infrastructure, equipment, personnel training, and tailored health promotion materials. This study contributes to the theoretical understanding of healthcare accessibility by applying the Andersen behavioral model. It highlights the practical implications for targeted interventions, policies, and resource allocation to enhance the capacity of healthcare facilities to provide accessible and inclusive health services to vulnerable populations during health emergencies.